Development of the Program to Enhance Creative Leadership Soft Skills of Teachers under Buriram Secondary Educational Service Area Office - Klumgen, Piyapat (Journal of Posthumanism, 2024)
This research aims to: 1) investigate the current situation, desired state, and necessary requirements for the development of creative leadership soft skills among teachers, and 2) develop a program to enhance these skills for teachers under the Buriram Secondary Educational Service Area Office. The study employs a mixed-methods approach, divided into two phases. Phase 1 examines the current and desired states, and the necessary requirements for the development of creative leadership soft skills among 345 teachers, selected through simple random sampling. Data were collected using a 5-point Likert scale questionnaire, and analyzed using frequency, mean, standard deviation, and need index statistics. Phase 2 involves developing a program to enhance these skills by conducting interviews with three purposively selected teachers using semi-structured interviews and analyzing the data using content analysis. Additionally, the program's feasibility and appropriateness were assessed by five experts through a 5-point Likert scale questionnaire, with data analyzed using mean and standard deviation. The results indicate that: 1) the current state of creative leadership soft skills among teachers was at a moderate level, while the desired state was at the highest level, and 2) the developed program included principles, objectives, content across five modules, development activities, and evaluation measures. The overall evaluation of the program's feasibility and appropriateness was rated at the highest level.